Screening anti-infectious molecules against Mycobacterium ulcerans: A step towards decontaminating environmental specimens - Hammoudi, Nassim (PLoS One, 2020)
Mycobacterium ulcerans, a non-tuberculous mycobacterium responsible for Buruli ulcer, resides in poorly defined environmental niches in the vicinity of stagnant water. Very few isolates have been confirmed. With a view to culturing M. ulcerans from such contaminated environmental specimens, we tested the in vitro susceptibility of the M. ulcerans CU001 strain co-cultivated with XTC cells to anti-infectious molecules registered in the French pharmacopoeia. We used a standardised concentration to identify molecules that were inactive against M. ulcerans and which could be incorporated into a decontaminating solution. Of 116 tested molecules, 64 (55.1%) molecules were ineffective against M. ulcerans CU001. These included 34 (29.3%) antibiotics, 14 (12%) antivirals, eight (6.8%) antiparasitics, and eight (6.8%) antifungals. This left 52 molecules which were active against M. ulcerans CU001. Three of the inactive antimicrobial molecules (oxytetracycline, polymyxin E and voriconazole) were then selected to prepare a decontamination solution which was shown to respect M. ulcerans CU001 viability. These three antimicrobials could be incorporated into a decontamination solution to potentially isolate and culture M. ulcerans from environmental samples.